Relations between open innovation and product quality: An empirical study of Japanese electronics firms - Takeshi Ishikawa; Hideo Suzuki (International Journal of Quality Innovation, 2018)
In late years, the concept of open innovation receives attention from industry and academic. This concept means that firms utilize resources outside for their R&D beyond their boundaries. Behind this background is the fact that firms have more opportunities to utilize resources outside. Previous studies indicate that by utilizing resources outside, firms could make R&D process more efficient or create new products. On the other side of the coin, we have to solve some aspects in open innovation context. First, product quality on the basis of activities of open innovation has to be defined. The definition of product quality is still unclear; thus, it is necessary to identify product quality in open innovation context. In addition, comparison between open innovation and in-company cooperation is not done so much. In the examination of effectiveness of open innovation, we should compare utilization of resources outside with that of in-company ideas. In this paper, we quantitatively analyze relations among product quality, utilization of resources outside, and utilization of internal resources on the basis of Covariance Structure Analysis. This analysis is based on a questionnaire survey at Japanese electronics firms in July 2015.
Keywords: 650; Open innovation; Product quality; In-company cooperation; Covariance structure analysis